Sub-10 ps Minimum Ionizing Particle Detection With Geiger-Mode APDs - Gramuglia, Francesco; Ripiccini, Emanuele; Fenoglio, Carlo Alberto; Wu, Ming-Lo; Paolozzi, Lorenzo; Bruschini, Claudio; Charbon, Edoardo (Frontiers in Physics, 2022)
Major advances in silicon pixel detectors, with outstanding timing performance, have recently attracted significant attention in the community. In this work we present and discuss the use of state-of-the-art Geiger-mode APDs, also known as single-photon avalanche diodes (SPADs), for the detection of minimum ionizing particles (MIPs) with best-in-class timing resolution. The SPADs were implemented in standard CMOS technology and integrated with on-chip quenching and recharge circuitry. Two devices in coincidence allowed to measure the time-of-flight of 180 GeV/c momentum pions with a coincidence time resolution of 22 ps FWHM (9.5 ps Gaussian sigma). Radiation hardness measurements, also presented here, highlight the suitability of this family of devices for a wide range of high energy physics (HEP) applications.